Barriers in Tuberculosis Treatment in Rural Areas (Tengger, Osing and Pandalungan) in Indonesia Based on Public Health Center Professional Workers Perspectives: a Qualitative Research - R Endro Sulistyono; Tantut Susanto; Rr Dian Tristiana (Universitas Airlangga, 2019)
Introduction: Tuberculosis (TB) is still one of the main health problems in Indonesia. Various efforts have been made by the government to handle the TB problem in Indonesia, one of which is implementing a direct observed therapy short course (DOTS) program. However, the handling of TB disease in Indonesia, especially in rural areas is still not optimal. This study aims to explore barriers to the handling of TB in rural areas from the perspective of public health center professionals.Methods: This study is a qualitative research with a phenomenological approach. Sampling was done by purposive sampling with a sample of 8 participants. Data is collected through focus group discussions. Thematic analysis is carried out using colaizi step.Results: This study obtained two themes. Theme 1 is the barriers in the aspect of TB patients and Theme 2, which is barriers from the aspect of health care facilities.Conclusion: This study obtained two themes. Theme 1 is the barriers in the aspect of TB patients and Theme 2, which is barriers from the aspect of health care facilities.